A novel environmental fate of graphene oxide: Biodegradation by a bacterium Labrys sp. WJW to support growth. (15th October 2018) - Qu, Yuanyuan; Wang, Jingwei; Ma, Qiao; Shen, Wenli; Pei, Xiaofang; You, Shengnan; Yin, Qingxin; Li, Xuanying
Abstract: Graphene oxide (GO) is a new type of nanomaterial with unique physicochemical properties and diverse applications, whereas it poses potential risk to human and environment. By screening from natural soil exposed to GO in the laboratory, we successfully obtained a novel bacterium, Labrys sp. WJW, which was able to use GO as the sole carbon source for growth. Within 8 days, cell numbers increased 16.76 ± 3.21 folds using 100 mg/L GO as the carbon source by qPCR analysis. The bacterial biodegradation which resulted in formation of holes and functional group changes of GO was proved by Raman spectroscopy, atomic force microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy analyses. Aromatic intermediates with structures of benzoic acid and phenol were identified using gas chromatograph-mass spectrometry and liquid chromatography/time-of-flight/mass spectrometry. Combination of genomic and proteomic analyses were performed to explore the proteins associated with GO degradation. A total of 644 proteins were significantly shifted. Bioinformatics analysis indicated that part of the up-regulated proteins were related to oxidation, ring cleavage and intermediates transmembrane processes, and GO was supposed to be degraded to benzoate and further degraded for downstream processes. This study enriches our understanding and provides new insights into the environmental fate of GO. Graphical abstract: Image 1 Highlights: Biodegradation of graphene oxide by bacterium. Labrys sp. WJW could use graphene oxide as the sole carbon source for growth. The proteins associated with graphene oxide degradation were explored. Graphene oxide was supposed to be degraded to benzoate and further degraded for downstream processes.